THE EFFECT OF USING KWL PLUS (KNOW, WANT, LEARN, PLUS MAPPING AND SUMMARIZING) STRATEGY ON STUDENTS’ READING COMPREHENSION - juwita kamalasari; rizki amelia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Reading is one of the most important skills that should be learned and mastered by individual. The purpose of this research was to find out wheter there was or not significant effect of using KWL Plus strategy on students’ reading comprehension at second grade of MTsN Kampar. This research was an experimental research. The research design was a quasi-experimental research. The total population of this research was the second grade students of MTsN Kampar. The sample was VIII.A as experiment class and VIII.B as control class taken by using cluster random sampling. Thus, the total number of sample from two classes was 56 students. The technique of analyzing data was an independent sample t-test by using SPSS 22 version program and Effect Size (ES) formula. The result showed that the effect of using KWL Plus strategy on students’ reading comprehension at the second grade at MTsNKampar, was 0.216 ≥ 0.14 or categorized into large effect. It can be concluded that there is significant effect of using KWL Plus strategy on students’ reading comprehension of narrative text at the second grade of MTsN Kampar.